Weathering the Storm So Far : The Impact of the 2003-05 Oil Shock on Low-Income Countries - Tadesse, Helaway; John, James; Lewis, Mark.; Zeuner, Jorg. (Washington, D.C. : International Monetary Fund, 2006)
This paper examines the impact of the 2003-05 oil price increase on the balance of payments positions and IMF financing needs of low-income country oil importers. It finds that stronger exports reflecting favorable global conditions, a compression of oil import volumes due to the pass-through of world prices to domestic consumers, and a large increase in capital inflows helped low-income countries cope with the oil price shock. Preliminary data suggest that reductions in oil import volumes have not harmed growth. While fiscal balances generally improved, quasi-fiscal liabilities may be building. Lower demand for IMF assistance may reflect broader trends, but further oil price increases could put pressure on additional countries in 2006 and beyond.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet